Faktor Determinan yang Berhubungan dengan Upaya Pengendalian Hipertensi di PSTW Budi Luhur Kota Jambi - Fithriyani Fithriyani; Miko Eka Putri (Jurnal Akademika Baiturrahim Jambi, 2020)
Aging is a natural process that can not be avoided, running continuously, and continuously. Based on population projection data the number of elderly people will increase where the most number is found at the age of 60-64 years 94,012 people. Increasing age decreases bodily functions, decreased organ function and changes in blood pressure, therefore the elderly are advised to check their blood pressure regularly. As they age, blood pressure in the elderly will increase so that there is a higher risk of developing hypertension. Hypertension is a major health problem throughout the world, causing a high prevalence and is associated with an increased risk of cardiovascular disease. Some things that need to be considered in an effort to control hypertension include regular exercise, adequate rest, medical, traditional, regulate diet and reduce salt consumption one teaspoon per day. The purpose of this study was to determine the determinants and factors associated with efforts to control hypertension in the elderly at PSTW Budi Luhur, Jambi City. The research method uses descriptive analysis design with cross sectional approach. Samples were conducted for the elderly with hypertension. The research instrument was in the form of questionnaire sheets by interview. The results obtained 40% of elderly people have a history of smoking, 45% are quite good in consuming food, 60% elderly with moderate activity and 60% elderly are good in controlling hypertension. The results of bivariate analysis showed that there was no correlation between determinant factors (smoking history, food consumption, physical activity) and hypertension control efforts in the elderly in PSTW Budi Luhur, Jambi City